ASSESSMENT OF SUSTAINABLE TOURISM USING SOCIAL, ECONOMIC, AND ENVIRONMENTAL INDICATORS: CASES STUDY OF BANJARNEGARA, INDONESIA - Sukmawati, Enra Riesti; Niyommaneerat, Wilailuk; Sakcharoen, Thammananya (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2022)
Sustainable tourism requires valuable and useful resources, balances people's social, economic, and environmental goals, and realizes the carrying capacity of resources. This paper examines the tourism situation in the City of Banjarnegara, Central Java, Indonesia, using the three pillars of sustainable tourism: Social, Economic and Environmental. This study aims to examine sustainable tourism in Banjarnegara by following indicators from the Global Council on Sustainable Tourism Destinations Criteria (GSTC-D) and publications in international journals using the keyword "indicator of sustainable tourism". The sampling technique used stakeholder analysis with purposive sampling by 21 expert respondents who have been involved in the world of tourism for approximately five years. Analysis of conditions in Banjarnegara compared with available indicators, then data validation by key stakeholder interviewing and respondents. The assessment of the indicators was followed by a questionnaire based on indicators; the measurement of indicators was carried out using a 5-point Likert scale by stakeholders to assess opinions from strongly disagree to strongly agree to obtain results where sustainable tourism indicators can become important indicators in Banjarnegara. In the end, the most important social, economic, and environmental indicators produced in this study can be used as sustainable tourism standards in Banjarnegara tourism development. Based on the assessment of social indicator questionnaire data, there are four social indicators in the strongly agree category with Total percentage of 89.67%. Based on the assessment of economic indicator questionnaire data, there are six economic indicators in the strongly agree category with total percentage of 87.94 %. Based on the assessment of environmental indicator questionnaire data, there are five economic indicators in the strongly agree category with total percentage of 86.27%.